Outcome of facial contour asymmetry after conventional two-dimensional versus computer-assisted three-dimensional planning in cleft orthognathic surgery - Po‐Jung Hsu; Rafael Denadai; Betty C. J. Pai; Hsiu‐Hsia Lin; Lun‐Jou Lo (2020)
Abstract Computer-assisted 3D planning has overcome the limitations of conventional 2D planning-guided orthognathic surgery (OGS), but difference for facial contour asymmetry outcome has not been verified to date. This comparative study assessed the facial contour asymmetry outcome of consecutive patients with unilateral cleft lip and palate who underwent 2D planning (n = 37)- or 3D simulation (n = 38)-guided OGS treatment for correction of maxillary hypoplasia and skeletal Class III malocclusion between 2010 and 2018. Normal age-, gender-, and ethnicity-matched individuals (n = 60) were enrolled for comparative analyses. 2D (n = 60, with 30 images for each group) and 3D (n = 43, with 18 and 25 images for 2D planning and 3D simulation groups, respectively) photogrammetric-based facial contour asymmetry-related measurements were collected from patients and normal individuals. The facial asymmetry was further verified by using subjective perception of a panel composed of 6 blinded raters. On average, the facial contour asymmetry was significantly (all p < 0.05) reduced after 3D virtual surgery planning for all tested parameters, with no significant differences between post-OGS 3D simulation-related values and normal individuals. No significant differences were observed for pre- and post-OGS values in conventional 2D planning-based treatment, with significant (all p < 0.05) differences for all normal individuals-related comparisons. This study suggests that 3D planning presents superior facial contour asymmetry outcome than 2D planning.